MARITAL SATISFACTION, INTERPERSONAL DEPENDENCY AND EMPLOYMENT STATUS PREDICTING GENERAL HEALTH STATUS AMONG MARRIED WOMEN IN NIGERIA - Njemanze, Vivian Chizoma; Onwukwe, Leonard C; Amandiogu, Ugochukwu A; Njoku, Ethelbert C; Ituma, Enuma (African Journal of Social and Behavioural Sciences, 2020)
This study investigated the influence of marital satisfaction, interpersonal dependency and employment status on general health status among married women in Owerri. Pearson correlation coefficient and multiple regression analyses were carried out on a sample of 300 married women selected through stratified random sampling techniques across communities in Owerri. The results show that interpersonal dependency was negatively related to health status. Contrary to expectations and previous findings, marital satisfaction was not significantly related to general health status while employment status was positively related to general health. However, marital satisfaction, interpersonal dependency and employment status jointly predicted general health status among married women. The study confirms the importance of employment status in the etiology of mental health problems among married women, and that the nexus between marital satisfaction, interpersonal dependency and employment status should be considered in the assessment of psycho-social problems. It also provided opposing data on previous studies conducted mostly on Western and individualist cultures which linked marital dissatisfaction to health disorders as a single predicting factor. This is underscored by the effect of the culture of merry-making and collectivism.